2013
DOI: 10.1007/s13538-013-0168-4
|View full text |Cite
|
Sign up to set email alerts
|

The Coevolution of Galaxies and Supermassive Black Holes in the Near Universe

Abstract: A fundamental role is attributed to supermassive black holes (SMBH), and the feedback they generate, in the evolution of galaxies. But theoretical models trying to reproduce the M SMBH − σ relation (between the SMBH mass and stellar velocity dispersion of the galaxy bulge) make broad assumptions about the physical processes involved. These assumptions are needed due to the scarcity of observational constraints on the relevant physical processes which occur when the SMBH is being fed via mass accretion in Activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…(iii) Inflows are observed in H 2 (e.g., Müller-Sánchez et al 2006;Riffel et al 2013b;Mazzalay et al 2014) in Seyfert galaxies and in low-ionization gas in LINERs (Fathi et al 2006;Storchi-Bergmann et al 2007;Schnorr-Müller al. 2011 with mass inflow rates in the range 10 −1 -10 1 M yr −1 (Storchi-Bergmann 2013. (iv) The stellar kinematics of Seyfert galaxies reveals cold nuclear structures composed of young stars, usually associated with a significant gas reservoir (Riffel et al 2010b(Riffel et al , 2011cStorchiBergmann et al 2012;Hicks et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(iii) Inflows are observed in H 2 (e.g., Müller-Sánchez et al 2006;Riffel et al 2013b;Mazzalay et al 2014) in Seyfert galaxies and in low-ionization gas in LINERs (Fathi et al 2006;Storchi-Bergmann et al 2007;Schnorr-Müller al. 2011 with mass inflow rates in the range 10 −1 -10 1 M yr −1 (Storchi-Bergmann 2013. (iv) The stellar kinematics of Seyfert galaxies reveals cold nuclear structures composed of young stars, usually associated with a significant gas reservoir (Riffel et al 2010b(Riffel et al , 2011cStorchiBergmann et al 2012;Hicks et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Radial velocity shifts of broad emission lines can also result from recoiling BHs (Herrmann et al 2007;Eracleous et al 2012), tidal disruption events (Gezari 2021), and gas outflows/ inflows (Brotherton et al 1994;Storchi-Bergmann 2010;Rakshit & Woo 2018;Kovačević-Dojčinović et al 2022). In addition, Barth et al (2015) found that Hβ velocity centroids can undergo dramatic changes, on timescales of a month, in response to continuum flux variations.…”
Section: Introductionmentioning
confidence: 99%